How Customer Avoidance Leads to Customers Returning: A Longitudinal Study Concerning Online Travel Agencies - Zerui Su; Hong-Youl Ha (Journal of Theoretical and Applied Electronic Commerce Research)
Customers’ intentions to avoid a product or service tend to be dynamic. Thus, this study aims to explore the influence of trajectory changes in customers’ avoidance after service recovery on relationship strength, negative word-of-mouth (WOM) intentions, and revisit intentions. Using a longitudinal approach with three-month lag intervals, we implement a latent growth model analysis to test our proposed hypotheses. Our findings demonstrate that customers’ desire to engage in avoidance after a service failure evolves, but its impact wanes. As avoidance decreases, negative WOM intentions likewise decline, and intentions to revisit a firm (which, in this study, is a travel agency) increase, thereby attenuating an avoidance-becomes-defection effect over time. Meanwhile, relationship strength initially grows but then weakens after service recovery. In contrast, negative WOM intentions slightly decrease from the early to mid-stage, followed by an increase in the late stage. Furthermore, relationship strength does not affect negative WOM or revisit intentions at the subsequent service recovery phase. Our findings offer innovative insights into upgrading customer avoidance perspectives regarding service recovery. We also present managerial implications regarding service recovery and customer relationship strategies that vary over time.